Strategi Penguatan Komitmen Organisasional Guru dalam Meningkatkan Efektivitas Program Guru Penggerak di Lingkungan SMA/K Kabupaten Bandung - Erif Deyussaswati; Nita Nurliawati; Teni Listiani; Edah Jubaedah (LPPM Institut Pendidikan Nusantara Global, 2026)
The Guru Penggerak Program (PGP) is a strategic initiative designed to strengthen teachers’ instructional leadership and improve educational quality in Indonesia. However, its implementation in senior high schools (SMA/SMK) in Kabupaten Bandung faces challenges, including inconsistent post-training mentoring and uneven impact dissemination. This qualitative descriptive-analytical study examines the program’s effectiveness, teachers’ organizational commitment, and strategies to enhance sustainable impact. Data were collected through in-depth interviews with Guru Penggerak teachers, principals, and supervisors, supported by participant observation and questionnaires from 34 teachers. Findings show that PGP is generally effective, fostering student-centered practices and increased teacher initiative, though its success depends on principal support. Teachers demonstrate strong affective commitment, moderate continuance commitment, and weaker normative commitment. Using the SOAR framework and 5-I stages, strategies are proposed across short-, medium-, and long-term phases to strengthen networks and integrate PGP values into school culture.